Inflammatory bowel disease in children - Putowski, Maciej; Padala, Olga; Krupa, Adrianna; Konopelko, Michał; Piasek, Ewa; Mazurek, Marek (Journal of Education, Health and Sport, 2019)
Pediatric inflammatory bowel diseases (IBDs), including Crohn disease (CD) and ulcerative colitis (UC), are chronic relapsing inflammatory disorders of the gastrointestinal tract. The incidence and prevalence of IBD is increasing, and approximately 25% of all patients are diagnosed before the age of 18 years. The pathogenesis of IBD is not fully understood but is thought to be mediated by dysregulated mucosal immune response, microbial dysbiosis, genetic and environmental factors. The presentation of IBD, especially in children and adolescents is variable, including both gastrointestinal and extraintestinal manifestations. The recommended diagnostic procedures of choice are ileocolonoscopy and esophagogastroduodenoscopy. IBD are diagnosed by the combination of clinical, pathological, endoscopic and serological features. The aims of therapy in pediatric IBD is to induce and maintain clinical remission, relieve symptoms, optimize growth, improve quality of life, and minimize toxicity as much as possible. The ECCO/ESPGHAN consensus guidelines include exclusive enteral nutrition, corticosteroids, 5-aminosalicylates, immunomodulators, biologics and surgery.